2021
DOI: 10.3390/ma14113025
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature on the Hydration Rate of Cements Based on Calorimetric Measurements

Abstract: The study presents results of calorimetric tests of three different cements. Two Ordinary Portland cements, CEM I 52.5 R and CEM I 42.5 R, and one Blastfurnace cement, CEM III/A 42.5 N LH/HSR/NA, were analysed. The analysis has shown that the empirical formulas derived based on the results can successfully replace the Arrhenius formula in determination of the hydration rate in relation to curing temperature. It was proven that the hydration rate in relation to the curing temperature changes with the progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The results from isothermal calorimetry are summarized in Figure 6 and are consistent with published data elsewhere and data from cement manufacturers [1,32]. An asterisk signalizes a crack-resistant cement according to the 40-day criterion of the ring shrinkage test as described in Section 3.2.…”
Section: Isothermal Calorimetrysupporting
confidence: 85%
“…The results from isothermal calorimetry are summarized in Figure 6 and are consistent with published data elsewhere and data from cement manufacturers [1,32]. An asterisk signalizes a crack-resistant cement according to the 40-day criterion of the ring shrinkage test as described in Section 3.2.…”
Section: Isothermal Calorimetrysupporting
confidence: 85%
“…Nevertheless, recognizing all hydration stages, especially the acceleration and deceleration periods, corresponds to the highest strength development. Different authors have stated that portlandite crystals grow into the interstices of the clinker grains during the acceleration period [44][45][46][47]. The C-S-H forms around the silicate clinker surfaces and successively grows into the pore solution.…”
Section: Specific Surface Area Of the Powders And Heat Release During...mentioning
confidence: 99%
“…The selection of temperature control and crack prevention measures is mainly based on temperature field research on mass concrete structures [ 1 , 2 , 3 ]. The temperature field of mass concrete is affected by internal and external factors [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, the internal factors of hydration and heat release from cementitious material are the key factors.…”
Section: Introductionmentioning
confidence: 99%
“…The hydration rate of concrete is influenced by internal factors such as cementitious materials dosage and variety and particle size [ 6 , 7 , 8 ], admixture type and dosage [ 9 , 10 , 11 , 12 ], water-binder ratio [ 9 ], aggregate type and dosage [ 5 , 13 ], and admixtures [ 14 ], as well as external factors including initial concreting temperature and ambient temperature [ 15 , 16 , 17 ]. Studies have shown that the initial concreting temperature and the water-binder ratio are two important kinetic factors affecting the hydration rate of concrete [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation